Use of Visual, Auditory, Kinesthetic (VAK) Models in Learning Mathematics on Curved-Sided Spatial Materials - Ulha Aulia Affandi; Lilik Hidayat Pulungan (Edumaspul: Jurnal Pendidikan, 2024)
This research was obtained due to the low direct participation of teaching participants in training. This research aims to identify comparisons using shapes or not using shapes. The use of forms is very important in ensuring the success of an educational process, the better the form used, the more efficient the target income, one of which is the VAK form. The visual auditory kinesthetic (VAK) form is a form of training that maximizes 3 learning styles in the form of visual, auditory and kinesthetic to make students feel safe. This research aims to look at the use of the VAK (visual, auditory, kinesthetic) form in Mathematics training for class IV students at SDN 167647 with the volume module of curved sided space shapes. The instrument used in this research is monitoring by looking directly using the VAK form in Mathematics with the volume module of curved sided shapes. After carrying out this research, you will find the desired success in the ongoing training.